Pediatric Sleep Questionnaire for Sleep Apnea in Newly Diagnosed Adolescent Idiopathic Scoliosis Patients - Ugur, Fatih; Topal, Kubra; Albayrak, Mehmet; Taskin, Recep (MDPI AG, 2023)
Close association has been established between obstructive sleep apnea (OSA) and adolescent idiopathic scoliosis (AIS), with PSQ being employed as a screening method for OSA. A cross-sectional study was conducted among patients aged from 10 to 16 years who presented to a scoliosis outpatient clinic. Patient demographics, radiological assessments, and PSQ scores were gathered. A total of 299 patients were included in the study, with 28.7% males and 71.2% females. The average Cobb angle was 6.20°. PSQ scores revealed a prevalence of 33.4% for significant obstructive sleep apnea. Patients diagnosed with AIS exhibited a prevalence of 32.9% with positive PSQ results. Among those undergoing adenoid and/or tonsil surgery, 27% had positive PSQ scores. Factors such as genetics, abnormal biomechanical forces, environmental factors including melatonin, and intermittent hypoxia were explored for their potential contribution to AIS etiology. The aim of the study is to underscore the importance of early detection and intervention in OSA cases and highlights the effectiveness of the PSQ, as a screening tool in identifying sleep disorders. The findings underscore the complex relationship between OSA and AIS, and moreover any spinal curvature is in relation with OSA.
Keywords: Article; 3. Good health